The Acute Effect of Hemodialysis on Choroidal Thickness - Osman Çelikay; Sinan Çalışkan; Tolga Biçer; Naciye Kabataş; Canan Gürdal (Journal of Ophthalmology)
Objective. To determine the effect of hemodialysis (HD) on choroidal thickness (CT). Methods. The right eyes of 41 patients with end-stage renal disease (ESRD) undergoing HD were included. All patients underwent an ophthalmic examination, including CT measurement via optical coherence tomography, intraocular pressure (IOP), blood pressure, and body weight measurement immediately before and after a HD session. Results. Mean subfoveal choroidal thickness (SFCT) after HD decreased significantly from 254.59 ± 84.66 µm to 229.34 ± 77.79 µm (p<0.001). CT at the temporal and nasal regions also decreased significantly after HD (both p<0.001). IOP changes after HD were insignificant (p=0.958). CT difference was insignificant in patients with diabetes mellitus (DM) and without DM before and after HD, respectively (p=0.285 and p=0.707). Stepwise multivariate linear regression analysis showed that diastolic blood pressure was the best fitted factor to explain the changes in CT (r=0.327 and p=0.040).  Conclusion. CT was decreased in the patients with ESRD following a HD session. This study suggested that the changes in CT may be related to the changes in systemic blood pressure.